PYELONEPHRITIS ETIOLOGY AND ITS DIAGNOSTICS - Ra’no Sh. Boltayeva; Nafisa B. Asatova; Dilnura M. Tolkinjonova (Central Asian Journal of Medicine, 2024)
In this article, the pathophysiology, clinical manifestations, diagnostic methods and treatment methods of pyelonephritis are analyzed in depth. Pyelonephritis is an infectious inflammation of the kidneys, mainly bacterial infections enter the body through the urinary tract and affect the kidney system. The main symptoms of the disease are characterized by fever, back pain, changes in urine. Laboratory and hardware methods, in particular, urinalysis and ultrasound examinations play an important role in diagnosis. Also, how antibiotics and other drugs and therapeutic measures are used in the treatment of pyelonephritis will be explained. The importance of early detection and effective treatment is emphasized.